Sosialisasi Perilaku Hidup Bersih dan Sehat serta Pemahaman Deteksi Dini Gejala Coronavirus Disease 2019 (Covid-19) - Nurlan, Nurlan; Fitriadi, Imam; Safnowandi, Safnowandi; Lukitasari, Diah; Suadi, Tajudin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The purpose of this activity is for people to know the importance of washing their hands properly, and what the impact will be if they don't wash their hands properly. The 2019 Coronavirus Disease (Covid-19) pandemic has caused all activities to be carried out individually in each village while adhering to the Covid-19 Standard Operating Procedure (SOP). The most common thing that is done in each activity is to provide education and demonstrations about Covid-19 to the surrounding community. In accordance with the Covid-19 rules, namely staying at home, the service implementing team conducted counseling by visiting residents' homes. Covid-19 is a new disease that emerged in 2019 and causes respiratory infections. The most common symptoms of Covid-19 are fever, dry cough and shortness of breath. Some people may experience head or body aches, runny nose, sore throat, or diarrhea. While some people (about 80%) will recover on their own from Covid-19 without needing special treatment, about 1 in 6 people will experience more serious symptoms and experience difficulty breathing. We are all at risk of contracting Covid-19, but older people and people with health problems such as high blood pressure, heart problems or diabetes, are more likely to experience severe symptoms from Covid-19, and are more at risk of dying from it. People with fever, cough and shortness of breath should seek immediate medical attention. People can catch Covid-19 from other people who are already infected, regardless of whether these people have symptoms or not. This disease can spread from human to other humans through droplets (droplets/splashes of body fluids from the nose or mouth, such as saliva). Droplets are spread when someone who already has this virus in their body coughs or sneezes. Research shows that Covid-19 can survive for some time on various inanimate surfaces, such as tables or doorknobs.